Sara Tarpuy: Sowing corn - Manya, Juan Antonio (1971)
In the time of the Inca, the sowing began with the festival of the tarpuy raymi, in the first days of August. The Inca, in front of his people, bowed to ask the Sun God for permission; then to the t'inkasqa with ñawin aqha and toasted with an appetizing chicha. Then, with the chakitajlla, he opened the earth, took a handful of earth that he kissed with love and respect before handing it over to an ajlla. The Willaq Umao, high priest, brought him selected seed that the Inca introduced into the hole along with fertilizer.